The Effectiveness of Emotional Freedom Technique (EFT) Therapy in Reducing Dysmenorrhea Pain Scale in Adolescents in Gampong Peunalom 2 Tangse, Pidie Regency - Mufida, Nurlela; Mua’lim, Azhar; Ismuntania; Nazari, Nuri (Trigin Institute, 2024)
Dysmenorrhea has an impact on disruption of daily activities in adolescents caused by menstrual pain. One way to reduce pain can be done by applying emotional freedom technique (EFT), which can be said to be the psychological version of acupressure therapy. EFT does not use needles, but rather aligns the body's energy system at the body's meridian points, namely by tapping with the fingertips. Research Objective: to determine the effectiveness of EFT therapy in reducing the pain scale of dysmenorrhoea in adolescents in Gampong Peunalom 2 Tangse, Pidie Regency. Research methodology: this research is quasi-experimental with a